Returning individual genetic results to research participants: experiences of stigma in South African families with neurodevelopmental disorders - Chetty, Nolene Priscilla (Department of Pathology, 2025)
In South Africa, there is little research about the experiences of stigma in parents or caregivers of children with a Neurodevelopmental Disorder (NDD). Likewise, the impact of genetic attribution on these experiences have not been extensively studied. The aim of this study was to explore the experiences of stigma of NeuroDev research participants and their families and how a positive genetic result influences/affects these experiences. To achieve this, the researcher looked at the experiences of parents or caregivers of NeuroDev research participants with stigma and the influence a positive genetic result may have on stigma experiences. The role of genetic counsellors in addressing instances of stigma in NDDs and genomics research was also considered. The study drew on an interpretive phenomenological approach (IPA) as this approach views individuals as “experiential experts” where researchers engage and interpret the meaning of experiences. This research was a sub-study to the NeuroDev study. The NeuroDev study aims to account for the lack of African genetic data of NDDs by exploring the phenotypic and genetic landscape of NDDs in South Africa and Kenya. Participants of the study included fathers, mothers or caregivers of children diagnosed with an NDD, who have voluntarily participated in the NeuroDev study and who have received a positive genetic result. This is a form of purposive sampling as participants were selected based on appropriateness for the aim and objectives of this study. Data collection and exploration involved semi-structured interviews with six participants to ensure that the data obtained was deeply associated with personal experiences, views and beliefs. Interviews were conducted at Red Cross War Memorial Children's Hospital or at the University of Cape Town between March 15th to April 14th 2023 and were audio-recorded. Interviews continued for 45-90 minutes so that the researcher obtained rich, meaningful data. Transcribed interviews were then analysed using an IPA-tailored thematic analysis flow to identify recurrent themes or patterns in the data. Findings show that participants experience public, associative and internalised stigma. It was further found that how a parent understands a diagnosis, the difficulty in raising a child with an NDD, and respective coping mechanisms affect how patients perceive a genetic result and, subsequently stigma. While a genetic result did not impact public stigma, some patients expressed that assigning meaning to a genetic cause impacts internalised stigma. Participants understanding of genetic counselling differed. Most expressed a lack of understanding of genetic counselling. Nonetheless, the genetic counselling session enhanced participants knowledge on NDDs, is patient-centred and impacted internalised stigma. It was expected that genetic counselling would have a greater impact on other forms of stigma, however, it was not seen in this study. This study forms a basis for future research to further elucidate experiences of stigma in parents or caregivers of children with NDDs and the role genetic counsellors may play in addressing this stigma and in genomics research in South Africa.